Particle emissions from microalgae biodiesel combustion and their relative oxidative potential. Issue 9 (4th August 2015) - Rahman, M. M.; Stevanovic, S.; Islam, M. A.; Heimann, K.; Nabi, M. N.; Thomas, G.; Feng, B.; Brown, R. J.; Ristovski, Z. D.
Abstract : Microalgae are considered to be one of the most viable biodiesel feedstocks for the future due to their potential for providing sustainable and cleaner alternatives to petroleum diesel. Abstract : Microalgae are considered to be one of the most viable biodiesel feedstocks for the future due to their potential for providing economical, sustainable and cleaner alternatives to petroleum diesel. This study investigated the particle emissions from a commercially cultured microalgae and higher plant biodiesels at different blending ratios. With a high amount of long carbon chain lengths fatty acid methyl esters (C20 to C22), the microalgal biodiesel used had a vastly different average carbon chain length and level of unsaturation to conventional biodiesel, which significantly influenced particle emissions. Smaller blend percentages showed a larger reduction in particle emission than blend percentages of over 20%. This was due to the formation of a significant nucleation mode for the higher blends. In addition measurements of reactive oxygen species (ROS), showed that the oxidative potential of particles emitted from the microalgal biodiesel combustion were lower than that of regular diesel. Biodiesel oxygen content was less effective in suppressing particle emissions for biodiesels containing a high amount of polyunsaturated C20–C22 fatty acid methyl esters and generated significantly increased nucleation mode particle emissions. The observed increase in nucleation mode particle emission is postulated to be caused by very low volatility, high boiling point and high density, viscosity and surface tension of the microalgal biodiesel tested here. Therefore, in order to achieve similar PM (particulate matter) emission benefits for microalgal biodiesel likewise to conventional biodiesel, fatty acid methyl esters (FAMEs) with high amounts of polyunsaturated long-chain fatty acids (≥C20) may not be desirable in microalgal biodiesel composition.